2014
DOI: 10.1002/asia.201402150
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Enzymes on 2‐Hydroxyethyl Methacrylate and Glycidyl Methacrylate Copolymer Brushes

Abstract: The immobilization of enzymes is of paramount importance to maintain their activity and stability. In this study, surface-initiated atom-transfer radical polymerization was applied to prepare poly(2-hydroxyethyl methacrylate)-block-poly(2-hydroxyethyl methacrylate-co-glycidyl methacrylate) brushes on glass slides. The polymerization kinetics was followed by using a quartz crystal microbalance with dissipation monitoring and ellipsometry in terms of mass and thickness growth, respectively. The surface chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 74 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…3-(2-Bromoisobutyramido)propyl triethoxy silane (BES) was synthesized according to literature [38,39]. Alkynylated peptide, KHIFSDDSSEK-Pra (KHI, Pra: L-Cpropargylglycine), was synthesized by Sangon Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…3-(2-Bromoisobutyramido)propyl triethoxy silane (BES) was synthesized according to literature [38,39]. Alkynylated peptide, KHIFSDDSSEK-Pra (KHI, Pra: L-Cpropargylglycine), was synthesized by Sangon Biotech (Shanghai, China).…”
Section: Methodsmentioning
confidence: 99%
“…20,21 The same tendency was found by Shang et al, who also confirmed that the amount of covalently immobilized glucose oxidase increased with the increase in thickness of the grafted poly(acrylic acid). 22 Further examples for this correlation were shown by the groups of Mao 23 and Gao, 24 who immobilized trypsin and lysozyme onto poly-(glycidyl methacrylate)-based brushes.…”
Section: Introductionmentioning
confidence: 96%
“…To create the β‐CD/azobenzene based responsible surface, hydrophilic poly(2‐hydroxyethyl methacrylate)‐ block ‐poly(2‐hydroxyethyl methacrylate‐ co ‐glycidyl methacrylate) (PHEMA‐ b ‐P(HEMA‐ co ‐GMA)) brushes were prepared via surface‐initiated atom‐transfer radical polymerization (SI‐ATRP) (Table S1, Supporting Information). β‐CD was immobilized on the polymer brushes via amino‐epoxy reaction for hosting azobenzene conjugated endothelial cells (ECs) selective Gly‐Arg‐Glu‐Asp‐Val (azo‐REDV) peptides. The surface property and cell mobility is adjusted by addition of competing guest molecules, adamantanamine hydrochloride (Ama), and UV light irradiation ( Figure ).…”
mentioning
confidence: 99%